Penyesuaian Santri Baru Terhadap Kegiatan di Pondok Pesantren Mahasiswi Al Husna - Achmadiannisa Putri Rahmanita Ashari; Alifa Nur Wijayanti; Ardy Rustu Irawan (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
The adjustment of new students is an individual process in carrying out the process of adjusting to the new activities and environment that they will occupy. In qualitative research, the aim is to explain and analyze the adjustment of new students to activities at the Al Husna Jember Student Islamic Boarding School. Researchers use the phenomenological approach method. Researchers used data collection techniques in the form of observation, documentation, and interview methods. The first result of the research is that there are two forms of adjustment of new students to activities at the Al Husna Student Islamic Boarding School, namely a good form of adjustment marked by obeying all the rules and carrying out obligations as students and the last form of adjustment is a wrong adjustment marked by the large number of new students who breaking the rules. The second is the process of adjusting the new students to activities at the Al Husna Jember Student Islamic Boarding School, there are two, namely the adjustment process that begins with a conflict caused by the compulsion of new students to enter the boarding school because their parents told them to. And what follows is an adjustment process without being based on conflict experienced by new students who have had the desire to enter and study religion at Islamic boarding schools from the start.